Methods for rural development projects: food security in practice - Hoddinott, John F. (International Food Policy Research Institute, 2001)
The International Food Policy Research Institute (IFPRI), like many development practitioners, often finds that insufficient information constrains its research efforts with partner organizations in developing countries. Solid data are often lacking on the nature of poverty, food insecurity, and malnutrition; the location of food insecure areas; and the causal links between potential interventions and outcomes of interest. This absence of information adversely affects the design, implementation, monitoring, and evaluation of interventions, including those designed to ameliorate food insecurity and malnutrition. This book, based on IFPRI’s field experience and interaction with a variety of partner organizations, aims to assist development practitioners in overcoming these constraints. The principal audience is an operational one — multilateral or bilateral aid agencies, nongovernmental organizations (NGOs), developing-country governments, and other development practitioners actively engaged in food security and nutrition issues. The book provides a framework for thinking about what projects would be most appropriate in a given situation and indicates what types of information are needed in order to maximize project impact. It can also assist by making development practitioners more fully conversant with food security and nutrition concepts.